Nuancing interdisciplinarity between and beyond liberal arts and professional education - Trinidad, Jose Eos (Perspective in the Arts and Humanities ASIA (formerly Asian Perspectives in the Arts and Humanities), 2020)
In an environment of ever-increasing cost of higher education and a precarious economic market, students and families labor over the right "major". Although many opt for technical and professional training, not a few still advocate for a liberal arts education. In this essay, I argue that interdisciplinary-or the integration of two or more disciplines - can be present in both liberal arts and professional education although they have differing aims, bases, and means, depending on the general field. Interdisciplinary in the liberal arts highlights humanistic questions, broad thinking, and understanding the whole. In technical professional education, it emphasizes practical problems, deep thinking, and understanding complexities. Highlighting the differences, however, is done not to separate them and lead to greater appreciation of the unique contribution of an interdisciplinary perspective of both fields of learning. Examples from a Philippine University are used to gound these ideas of distinguishing and connecting interdisciplinary in liberal arts and professional education